Analisis Pengaruh MÂ¬anajemen Rantai Pasokan terhadap Performa Bisnis (Studi: Pedagang Grosir Tradisional Makanan dan Minuman Ringan Tradisional di Kabupaten Banyumas) - Ramadan, Yanuar Sidik; Kusumawardhani, Amie (Faculty of Economics and Business Diponegoro University, 2017)
In a tight business competition, supply chain management (SCM) plays a significant role in supporting business performance. This study aims to analyze the effect of supply chain management on business performance. Three dimensions of SCM: relationship with customers, relationship with suppliers, and human capital were investigated in this study.Population of this study is traditional snack and soft drink wholesalers in Kabupaten Banyumas. As many as 125 respondents, who have been in the business for at least one year, were selected as a sample. Data was analyzed using Structural Equation Modelling (SEM) and processed applying AMOS 22 as an analytical tool.Findings of the study shows that relationship with costumers as well as with suppliers and human capital have positive and significant effects on competitive advantage. Likewise, competitive advantage was found to have a positive and significant effect on business performance.This study reveals that traditional snack and soft drink wholesalers in Kabupaten Banyumas might improve their business performance by applying supply chain management.